Novel Developments in the Prevention, Diagnosis, and Treatment of Periprosthetic Joint Infections. (April 2015) - Parvizi, Javad; Alijanipour, Pouya; Barberi, Elie F.; Hickok, Noreen J.; Phillips, K. Scott; Shapiro, Irving M.; Schwarz, Edward M.; Stevens, Michelle H.; Wang, Yi; Shirtliff, Mark E.
Abstract : Periprosthetic joint infection (PJI) is one of the most challenging complications compromising the outcome of an otherwise successful operation. Considerable efforts have been invested in the recent years to address paradigm shifts in our understanding of the complex microbiological phenomena that contribute to the pathophysiology of PJI, such as microbial adherence, biofilm formation, and resistance to antibiotics. This article is an introduction to some of the recent advancements in the prevention, diagnosis, and treatment of PJI. It describes how industry, academic researchers, and government are increasing collaboration to address PJI through development of novel technologies, therapeutic strategies, and regulatory science that specifically target the unique biofilm-associated aspects of its pathogenesis.